The chronic renal disease course: from early symptons to discovery - Fortes, Vera Lucia Fortunato; Bettinelli, Luiz Antonio; Pomatti, Dalva Maria; Brock, Jordana; Dobner, Taise (Rev Rene, 2013)
An exploratory and descriptive study with a qualitative approach aim at understanding the significance of the discovery of chronic kidney disease and the need for the hemodialysis machine. The research was made with twenty patients from two hemodialysis services of the city of RS. The data collection took place between September and December of 2007, throughout semi-structured interviews. The thematic analysis generated the following categories: history of chronic kidney disease, from the silence of the disease to the classical clinical symptoms; the discovery and its immediate effects; life after the discovery; acceptance of the dependence on a machine. We conclude that there is a need to adapt the daily life of patients with chronic kidney disease, because the hemodialysis causes physical and social changes, requiring support from health-team to manage the disease. The professional should not abdicate knowledge, safety and technical skill, as requirements to care.DOI: https://doi.org/10.15253/2175-6783.2013000300009